ANALISIS GERAK PEMAKANAN DAN JENIS MEDIA PENDINGIN TERHADAP KEKASARAN PERMUKAAN LOGAM HASIL PEMBUBUTAN PADA MATERIAL SUS304 - Kurniawan, Yogi; Herawan, Budi; Indrayani, Novi Laura (Jurnal Ilmiah Teknik Mesin, 2019)
Surface roughness of a product plays an important role, especially for materials such as SUS 304 steel which is now widely used in a variety of industrial needs. Determination of the turning parameters or the appropriate type of cooling fluids are very important to obtain the desired surface roughness. The aim of the study was to determine the ideal value of feeding (f) and the ideal type of cooling fluids in the turning process of SUS 304 steel. The feedrate parameters used were 0.11 mm/rev, 0.15 mm/rev, and 0.19 mm/rev, whereas the types of cooling fluids used are Fumio Lube Fumicool 794 soluble oil and Suncut 16S lubricant oil. Surface roughness results are obtained through testing using a surface roughness measuring instrument. From the predetermined parameters were obtained the smallest roughness value on the feedrate was 0.11 mm/rev using Suncut 16S lubricant oil with a result of 0.770 Âµm, while the largest roughness value on the feedrate was 0.19 mm/rev using Fumio Lube Fumicool 794 soluble oil with a result of 3.942Âµm.